2018
DOI: 10.3390/cli6030069
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Global Horizontal Irradiance Estimates through BSRN, TOACs and Air Temperature/Sunshine Duration Test Procedures

Abstract: Solar Radiation (SR) data are required for many disciplines and applications. The ground measurement of SR data is hampered by technical and operational errors. Therefore, several approaches have been developed to detect these errors. This study aimed to compare two quality tests of hourly Global Horizontal Irradiance (GHI) estimates through the Baseline Surface Radiation Network (BSRN) of the World Meteorological Organization (WMO) and Top of Atmosphere irradiance and Clear sky (TOACs) on a horizontal plane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The high rates of positive bias and RMSE at Kalar compared to all of the other stations (Figures 7-11) might be due to the quality of the recorded data [46] and a partial shadow on the sensor at that station, because its mean is lower than that at the other stations by nearly 30 W/m 2 (Table 3), while those data have passed the quality check. However, a similar positive bias and RMSE are reported by other studies [41,42].…”
Section: All-sky Conditionsmentioning
confidence: 97%
See 2 more Smart Citations
“…The high rates of positive bias and RMSE at Kalar compared to all of the other stations (Figures 7-11) might be due to the quality of the recorded data [46] and a partial shadow on the sensor at that station, because its mean is lower than that at the other stations by nearly 30 W/m 2 (Table 3), while those data have passed the quality check. However, a similar positive bias and RMSE are reported by other studies [41,42].…”
Section: All-sky Conditionsmentioning
confidence: 97%
“…The two datasets were harmonised for true local solar time. All of the GHI ground data were tested with the BSRN tests [45] and other quality control tests [46,47]. Full information about the quality control of the ground data in this study can be found in [46].…”
Section: Quality Controal Of Ghi Measurmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full quality control procedure was applied to all nine stations of ground measurements to detect systematic errors, to select questionable data and to find gaps and not applicable (NA) values. The quality control procedure is published in a study with full details [73].…”
Section: Quality Control Of Ghi Measurements and Evolution Of Sddsmentioning
confidence: 99%
“…The output data from the nine stations in the study area in the two mentioned studies from which ground measurements were tested [73] and SDDs were evaluated [30], were used in this study.…”
Section: Quality Control Of Ghi Measurements and Evolution Of Sddsmentioning
confidence: 99%